I'm your man ebook The life of leonard cohen. - Simmons, Sylvie (2024)
"The major, soul-searching biography that Leonard Cohen deserves [from] a seasoned rock journalist" (Janet Maslin,  New York Times ). Leonard Cohen is one of the most important and influential musical artists of the past fifty years—and one of the most elusive. In  I'm Your Man , journalist Sylvie Simmons, one of the foremost chroniclers of the world of rock 'n' roll and popular music, explores the legendary singer/songwriter's extraordinary life and creative genius. I'm Your Man  is an intimate and insightful appreciation of the man responsible for "Suzanne," "Bird on a Wire," "Hallelujah," and so many other unforgettable, oft-covered ballads and songs. Based on Simmons's unparalleled access to Cohen—and written with her hallmark blend of intelligence, integrity, and style— I'm Your Man  is the definitive biography of a major musical artist widely considered in a league with the great Bob Dylan. Readers of  Life  by Rolling Stone Keith Richards and Patti Smith's phenomenal  Just Kids  will be riveted by this fascinating portrait of a singular musical icon.